The Effect of Human Resource Development on Employee Performance - Rizqi Saputra, Muhammad; Darka, Darka; Saputro, Allya (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Human resources have a major role in every organization. Even though it is supported by facilities and infrastructure and other resources, it is not supported by reliable human resources. And this research are use quantitative method. Based on the results of research and discussions that have been carried out in this research regarding the influence of human resource development on employee performance at PT.  Eka Bogainti, Jakarta City, the researcher drew several conclusions and suggestions as follows, Human resource development partially has a positive and significant effect on employee performance PT. Eka Bogainti, Jakarta City. This states that the hypothesis is accepted and proven to be accepted as true, Formal development partially has a positive and significant effect on employee performance PT. Eka Bogainti, Jakarta City. This states that the hypothesis is accepted and proven to be true. Based on the conclusions that have been obtained, the following suggestions can be given, for the leadership of PT Asuransi Jiwa Prudential Medan Branch to pay attention to the informal development of employees, For the leadership to pay attention to and improve the formal development of employees.